PENERAPAN ERGONOMI DENGAN METODE RAPID ENTIRE BODY ASSESSMENT (REBA) UNTUK MENGURANGI RISIKO CEDERA PADA PROSES PENJEMURAN KERUPUK DI UMKM KERUPUK SUBUR - Samau’al Dhani Putra Hartono; Jonat Jannata Tampana Putra; Fachrizal Nazir Nugroho; Achmad Tazaki Al Mamtuh; Fani Nugroho; Ayudyah Eka Apsari (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Abstract. The cracker drying process at the Kerupuk Subur MSME is still carried out manually with non-ergonomic work postures, such as bending, lifting, and reaching repeatedly, which have the potential to cause musculoskeletal complaints. This study aims to identify worker complaints, analyze the level of work posture risk, and design an ergonomic drying table to reduce the risk of musculoskeletal disorders (MSDs). The methods used include the Nordic Body Map (NBM) to identify worker complaints, Rapid Entire Body Assessment (REBA) to assess work posture risks, and Quality Function Deployment (QFD) to translate worker needs into technical specifications for table design. The NBM results show dominant complaints in the waist, back, shoulders, wrists, and knees with a high risk category, while the REBA results in the initial condition obtained a score of 7 (moderate risk) which then decreased to 1 (very low risk) after the ergonomic table design was carried out. The application of QFD resulted in a drying table design that suits worker needs, including aspects of comfort, strength, flexibility, and ease of movement. The results of this study indicate that ergonomic drying tables can improve work posture and significantly reduce the risk of musculoskeletal disorders. Keywords: ergonomics, Nordic body map, REBA, QFD, musculoskeletal disorders, drying tables.